Pendidikan Antikorupsi di Kalangan Pesantren: Ulasan Buku Jihad Nahdlatul Ulama Melawan Korupsi - Ibrahim, Maulana Hafidz; Ridwan, Auliya (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2023)
Anti-corruption education is an imperative that necessitates development within Indonesia, given the recent surge in instances of corruption ranging from the grassroots level to the highest echelons of the state. Islamic boarding schools, known as pesantren, hold significant potential in combating corruption within the country. In this context, Marzuki Wahid and his colleagues have formulated ideas encapsulated in the book